2018
DOI: 10.1016/j.mimet.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A senescence-delaying pre-culture medium for transcriptomics of Podospora anserina

Abstract: Podospora anserina is an efficient degrader of recalcitrant plant biomass but senesces quickly on most standard pre-culturing media. Among nine pre-culture media, sufficient growth without senescence was only observed on Luria-Bertani medium. The high quality RNA obtained from subsequent transfer cultures was suitable for transcriptomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To simplify the detection of early markers of ligninolytic activity of P. anserina, we used cultivation conditions that would allow us to evaluate changes in both lignin structure and in the fungal secretome [21]. To this end, we incubated the fungus on pre-isolated lignin from wheat straw that was combined with the hemicellulose fraction of the straw, i.e., glucuronoarabinoxylan (GAX), instead of growing the fungus on unfractionated wheat straw.…”
Section: Cultivation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…To simplify the detection of early markers of ligninolytic activity of P. anserina, we used cultivation conditions that would allow us to evaluate changes in both lignin structure and in the fungal secretome [21]. To this end, we incubated the fungus on pre-isolated lignin from wheat straw that was combined with the hemicellulose fraction of the straw, i.e., glucuronoarabinoxylan (GAX), instead of growing the fungus on unfractionated wheat straw.…”
Section: Cultivation Setupmentioning
confidence: 99%
“…Media and growth conditions for P. anserina were based on previously described procedures [21,60]. Waterinsoluble wheat glucuronoarabinoxylan (GAX, Megazyme, Wicklow, Ireland, 100 mg) and GAX (100 mg) combined with wheat straw lignin isolate (100 mg) were dispersed in 5 mL M2 minimal medium in 40-mL flasks and autoclaved prior to inoculation.…”
Section: Growth Of Podospora Anserina On Wheat Straw Ligninmentioning
confidence: 99%
“…This tentatively suggests that they may act through the activation of specific pathway(s), rather than having general roles in modulating the redox status of the substrate. This is substantiated by the fact that lignin modulates transcription in P. anserina [74]. Interestingly, improved growth and fertility triggered by lignin may be a general phenomenon in fungi, since it was previously demonstrated that lignin increases growth and fruiting body production in the basidiomycete shitake [75] and that extractives stimulate the production of perithecia in Chaetomium indicum and Chaetomium globosum [76], two fungi closely related to P. anserina.…”
Section: Discussionmentioning
confidence: 93%
“…This indicated that LB broth medium could be a suitable medium for Iranian Lizard Leishmania culture and recombinant protein production compared with the RPMI1640 medium, brain heart infusion medium and M199 medium [ 3 ]. Another study found that the good growth without senescence of Podospora anserina was observed only on LB medium, which prolonged the health of the mycelium, while liquid cultures without senescence were observed only in LB broth medium [ 4 ]. Taken together, in life science experiments, LB broth medium is the preferred bacterial growth solution for almost all microbes, including bacteria, fungi, and parasites.…”
Section: Introductionmentioning
confidence: 99%